Political Communication Strategy for Governorship Elections in Southeast Sulawesi Province Through Ethnicity Approach - Hamrin Hamrin; Kumba Digdowiseiso; Muhammad Dimyati Sudja (Budapest International Research and Critics University, 2022)
Communication strategies with the ethnicity approach of the Southeast Sulawesi Governor election are one of the keys to success in collecting votes. This study aims to determine the Political Communication Strategy in the Governorship Election in Southeast Sulawesi province through the Ethnicity Approach and to find out the factors of supporting and inhibiting the Political Communication Strategy in the Governor election through the ethnicity approach. This research is a type of qualitative research with a descriptive analysis approach. Data obtained through literature studies. The results showed that now, over time and the rapid development of communication technology, the issue of ethnicity still continues to be used by candidates to get the most votes. Many uses social media with a pattern of ethnicity approach at the time of the campaign to attract as many masses as possible and to vote. For example, during the Southeast Sulawesi gubernatorial election with a pattern of ethnicity approach, they were able to get the most votes to win the democratic party